Agar-Based Disc Diffusion Assay for Susceptibility Testing of Dermatophytes in the Rajshahi Region (TAJ: Journal of Teachers Association, 2022)
Background: Dermatophytosis is considered one of the most common public health problems in the world and is the most commonly diagnosed skin disease in Bangladesh. The prevalence and types of dermatophyte infections vary with climate conditions, age, lifestyle, and population migration patterns. Depending upon the anatomical site of the lesion, dermatophytes are classified into different varieties.  Objective: To isolate dermatophytes and their antifungal susceptibility pattern by agar-based disc diffusion method in the Rajshahi region.Materials and Methods: Clinical samples (e.g., skin scrapings, nail clipping, and hair plucking) were collected under aseptic precautions. The identification of dermatophytes was performed through a microscopic examination using 10% KOH mount, mycological culture, and species identification by lactophenol cotton blue mount from culture. In addition, all dermatophytes isolates were subjected to antifungal susceptibility testing using the agar-based disc diffusion method.Results: Out of 171 samples, Trichophyton rubrum was the predominant dermatophyte species with 76(71.7%), followed by T.mentagrophyte were 15(14.2%), E. floccosum were 12(11.3%), and M. canis were 03(2.8%). Voriconazole and Itraconazole were more effective drugs. Griseofulvin was the least effective drug, followed by Fluconazole.Conclusion: Despite several treatment options being available for cutaneous fungal infections, Due to the increasing trend of antifungal drug resistance among dermatophytes, treatment should be based on antifungal sensitivity testing. The disc diffusion method is a simple and valuable method for the evaluation of antifungal susceptibility of dermatophytes.TAJ 2022; 35: No-1: 99-106